Muthaliyar Kalveddu’: preserving Tamil history - a Librarian’s perspective - Kupeshan, R.; Chandrasekar, K.; Menusha, K.; Thanuja, S. (Eastern University, Sri Lanka, 2025)
Documenting and preserving cultural heritage is a crucial endeavor undertaken by libraries, museums and archives worldwide to ensure wider access and safeguard unique, rare information resources. Sri Lanka possesses a vast collection of cultural heritage documents, many of which remain under constant threat from natural disasters and by other means. Unfortunately, lack of proper preservation and conservation efforts has led to the irreversible loss of many invaluable materials, often without a copy for future reference. The University of Jaffna, a leading academic institution in the Northern region of Sri Lanka with a rich history spanning 50 years, recognizes the preservation and conservation of cultural and scholarly assets as a vital responsibility. Despite challenges such as limited resources, inadequate infrastructure, and constrained technological support, the Jaffna University Library remained resilient, even during periods of civil unrest, striving to preserve and safeguard the rich historical heritage of the Tamil community. As part of this commitment, the palm-leaf manuscript collection housed in the Archives of the Jaffna University Library stands as a unique repository of Sri Lankan Tamil heritage, preserving an invaluable cultural legacy for future generations. This study focuses on the Muthaliyar Kalveddu (Catalogue No. 162), a palm-leaf manuscript composed on March 26, 1873, by Rajasekhara Subramaniam Muthaliyar of Ottisuttan, which is preserved in the Jaffna University Library. The study aims to explore the socio- economic, political, and cultural significance of this manuscript, identify suitable conservation methods for its preservation, and highlight efforts made for knowledge dissemination. A historical descriptive approach was employed toexamine the Muthaliyar Kalveddu manuscript in detail, which provided a comprehensive account of historical facts and trends. The Muthaliyar Kalveddu manuscript consists of 18 leaves, measuring 27.5 cm in length and 3.0 cm in width. It provides a historical account of Sri Lanka’s Northern Province, tracing its history from the Ramayana period to the Jaffna Kingdom, with particular emphasis on the kingdom’s expansion into Vannipattu after the reign of King Pararasasekharam of Jaffna. The manuscript also documents the existence of various groups of people, including Atangapattai Vedar, Parayar, Rakshas, Parangyars, Ampatars, and Paravars. It also describes how, with the migration of people, ponds and water bodies were constructed to meet domestic needs, and 18 caste-based industries were established to serve the growing population. Furthermore, the manuscript reveals that during this period, pearling played a significant role in the local economy, and maritime trade flourished through the Mannar port, facilitating connections with India. It also mentions the construction of parks for recreation and the religious practices of the people, who worshiped Lord Shiva and village deities such as Nachimar and Annamar. In the conservation process, a mixture of lemongrass oil and alcohol was used to clean the palm leaves, after which the manuscripts were left to dry naturally. They were then wrapped in red cotton cloth, secured with twine, and stored in wooden cabinets for safekeeping. At the same time, efforts are underway to digitize and reproduce the manuscript in order to ensure the longevity of the original manuscript and facilitate knowledge dissemination, respectively. As custodians of information resources, librarians hold the responsibility of ensuring the conservation and preservation of archival materials and safeguarding this valuable knowledge for future generations.
Keywords: Palm-leaf manuscripts; Ola leaves; Conservation and Preservation; Tamil cultural heritage